Identification of key genes and pathways revealing the central regulatory mechanism of brain-derived glucagon-like peptide-1 on obesity using bioinformatics analysis - Shao, Yuwei; Tian, Jun; Yang, Yanan; Hu, Yan; Zhu, Ye; Shu, Qing (Frontiers in Neuroscience, 2022)
Objective: Central glucagon-like peptide-1 (GLP-1) is a target in treating obesity due to its effect on suppressing appetite, but the possible downstream key genes that GLP-1 regulated have not been studied in depth. This study intends to screen out the downstream feeding regulation genes of central GLP-1 neurons through bioinformatics analysis, and verify them by chemical genetics, which may provide insights for future research. Methods: GSE135862 genetic expression profiles were extracted from the Gene Expression Omnibus (GEO) database. The gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes pathway (KEGG) enrichment analyses were carried out. STRING database and Cytoscape software were used to map the protein-protein interaction (PPI) network of the differentially expressed genes (DEGs). After bioinformatics analysis, we applied chemogenetic methods to modulate the activities of GLP-1 neurons in the nucleus tractus solitarius (NTS), and observed the alterations of screened differential genes and their protein expressions in the hypothalamus under different excitatory conditions of GLP-1 neurons. Results: A total of 49 DEGs were discovered, including 38 down-regulated genes and 11 up-regulated genes. The two genes with the highest expression scores were biglycan (Bgn) and mitogen-activated protein kinase activated protein kinase 3 (Mapkapk3). The results of GO analysis showed that there were ten molecular functions of differential genes. Differential genes were mainly localized in seven regions around the cells, and enriched in ten biology processes. The results of KEGG signaling pathway enrichment analysis showed that differential genes played an important role in seven pathways. The top 15 genes selected according to the Cytoscape software included Bgn and Mapkapk3. Chemogenetic activation of GLP-1 in NTS induced decrease in food intake and body mass, while Chemogenetic inhibition induced opposite effect. The gene and protein expression of GLP-1 were upregulated in NTS when activated by chemogenetics. In addition, the expression of Bgn were up-regulated and that of Mapkapk3 were down-regulated in hypothalamus. Conclusions: Our data showed that GLP-1 could modulate the protein expression of Bgn and Mapkapk3. Our findings elucidated the regulatory network in GLP-1 to obesity and might provide a novel diagnostic and therapeutic target for obesity.